Simpus Apus Sirenomelia – A case report of a rare congenital anomaly (Indian Journal of Case Reports, 2015)
Sirenomelia, also known as “mermaid syndrome”, is a rare congenital deformity of uncertain etiology. Sirenomelia is characterized by complete or partial fusion of lower limbs, giving the appearance of the tail of a ‘mermaid’. This syndrome is almost always lethal due to associated congenital visceral abnormalities such as severe lung hypoplasia, and abnormalities of the kidneys, large intestines, and genitalia. We hereby, report a case of sirenomeila due to rarity of this condition and term live birth.